Determinan Pemeriksaan Payudara Sendiri (SADARI) pada Mahasiwi Fakultas Kesehatan Masyarakat Universitas Nusa Cendana Kupang Tahun 2023 - Tari, Tirza; Landi, Soleman; Tejdu Hinga, Indriati A (Yayasan Literasi Sains Indonesia, 2023)
Breast self-examination (BSE) is a method of early detection of breast cancer. Females can use it to check the condition of their breasts. BSE is effective in detecting abnormalities in the breast early to find immediate treatment. This study aims to determine the determinants of BSE in female students at the Faculty of Public Health, Nusa Cendana University in Kupang. This type of research is quantitative with a cross-sectional study design. This research was conducted at the Faculty of Public Health with a sample of 300 female students. The data analysis used was univariate and bivariate analysis with the chi-square statistical and contingency coefficient test. Statistical test results show that there is a fairly strong relationship between knowledge (ρ-value = 0.000; C = 0.509) and information exposure (ρ-value = 0.000; C = 0.353) and a strong relationship between attitudes (ρ-value = 0.000; C = 0.622) with BSE, there is no relationship between family history (ρ-value = 0.128) and parental support (ρ-value = 0.675) and BSE. As has been demonstrated, this study's independent variables, which consisted of knowledge, attitudes, and information exposure, were related to BSE and the independent variables. It consists of family history and parental support that were unrelatable to BSE in female students of the Faculty of Public Health, Nusa Cendana University in Kupang. Female students need to play an active role in finding information related to BSE and be able to perform BSE regularly in the correct steps. Anticipatively, Kupang City Health Office can increase health promotion efforts through various media, especially counseling/socialization about BSE regularly.